Quantifying hospital plate waste and identifying its correlates from patients’ perspectives in Lebanon - Maha Hoteit; Nour Badreddine; Jana El Cheikh Mohamad; Maroun Khattar; Ferial Fattouh; Dana Malli; Esraa Antar; Sami El Khatib; Mohamad G. Abiad; Hussein F. Hassan (Scientific Reports)
Abstract Hospital plate waste poses a major challenge facing the present food systems, as providing meals that meet the nutritional requirements and expectations of the patients remains complex for hospital food services. This study aimed to assess the magnitude of plate waste in Lebanese hospitals, evaluate the patients’ satisfaction levels, and identify the determinants of plate waste in participating hospitals. A cross-sectional study was conducted between April 2023 and September 2023, involving 155 in-patients from cardiovascular, gastrointestinal, obstetrics-gynecology, and surgical wards across 16 hospitals in different Lebanese governorates. Plate waste was measured, and patient satisfaction was assessed using a questionnaire. Plate waste represented 31.4% of the total food served, equivalent to 366 tonnes annually in the 16 participating hospitals. Waste was higher in hospitals located in rural areas (p-value = 0.771). The highest waste levels were observed in the obstetrics-gynecology ward and during lunchtime. Vegetables were the most wasted food group. The majority of participants were satisfied with the food service, and low appetite was the main reason for not consuming hospital meals. Food quality (β= −0.17, p-value = 0.049) and governorate (β= −0.18, p-value = 0.019) were determinants of plate waste. The hospital sector is as unique and challenging as other sectors regarding plate waste, which warrants further research to gain deeper insights into waste generation.